2020
DOI: 10.3389/fmicb.2020.01544
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Produced by the Probiotic Propionibacterium freudenreichii CIRM-BIA 129 Mitigate Inflammation by Modulating the NF-κB Pathway

Abstract: Immunomodulatory Propionibacteria EVs EVs, alongside their physicochemical, biochemical and functional characterization. This study has enhanced our understanding of the mechanisms associated with the probiotic activity of P. freudenreichii and identified opportunities to employ bacterial-derived EVs for the development of bioactive products with therapeutic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 83 publications
5
54
0
Order By: Relevance
“…Accordingly, the SlpB protein purified from P. freudenreichii was shown to mitigate inflammation in human intestinal epithelial cells (do Carmo et al, 2017;Rabah et al, 2018a,b). Furthermore, P. freudenreichii was shown to produce extracellular vesicles containing the SlpB protein which are also involved in modulating host cell inflammation (Rodovalho et al, 2020). These results are in line with recent findings that identified propionibacteria as commensals within the gut microbiota of healthy infants (Colliou et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
“…Accordingly, the SlpB protein purified from P. freudenreichii was shown to mitigate inflammation in human intestinal epithelial cells (do Carmo et al, 2017;Rabah et al, 2018a,b). Furthermore, P. freudenreichii was shown to produce extracellular vesicles containing the SlpB protein which are also involved in modulating host cell inflammation (Rodovalho et al, 2020). These results are in line with recent findings that identified propionibacteria as commensals within the gut microbiota of healthy infants (Colliou et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
“…The number of proteins detected in Sis-EVs is considerably higher than that reported previously for EVs from S. acidocaldarius, S. solfataricus and S. tokodaii [49], possibly due to improved sensitivity of massspectrometry over the past decade. Notably, recent studies on the proteomics of EVs produced by diverse bacteria [70][71][72][73] as well as halophilic archaea [18] report the presence of hundreds of proteins in each type of EVs, consistent with our results. For instance, it has been shown that EVs produced by halophilic archaeon Halorubrum lacusprofundi contain 447 different proteins [18].…”
Section: Protein Content Of Sis-evssupporting
confidence: 92%
“…Negative staining electron microscopy was performed as previously described ( Rodovalho et al, 2020 ) to investigate the shape and integrity of purified EVs. EVs samples were diluted, and solutions containing between 10 10 and 10 11 particles per ml were analyzed.…”
Section: Methodsmentioning
confidence: 99%